A new species of Cephalochetus Kraatz, 1859 (Coleoptera: Staphylinidae: Paederinae) from Mêdog, China - Li, Xiao-Yan; Ma, Hong-Ye; Wang, Lin-Fei; Pan, Zhao-Hui; Lü, Liang (Zootaxa, 2026)
A new species of Cephalochetus Kraatz, 1859 from China is described: Cephalochetus zhangguohuai sp. nov. collected from Mêdog County, Xizang, China. Color plates of the habitus, maxillary palpi, abdomen with sternites and tergites of the males, as well as the aedeagal structures are provided.